The Independence of Bodily Harm An Analytical Study (مجلة دراسات إقلیمیة, 2026)
Research Idea: Bodily harm is one of the most significant forms of injury affecting individuals, alongside material and moral harm. It directly affects bodily integrity and gives rise to important legal consequences. The concept of bodily integrity is based on the principle that the right to physical integrity attains its full value only when the body remains complete and free from impairment.Objective: The research aims to clarify the concept of bodily harm and analyze its legal nature within the framework of civil liability, with particular emphasis on its independence from material and moral harm.Methodology: The research adopts an analytical approach through the examination of legal scholarship on bodily harm and its relationship to other forms of harm.Results: The findings indicate that bodily harm possesses distinctive characteristics that differentiate it from material and moral harm, as it affects the individual's right to bodily integrity, an inherent right attached to human personality.Conclusion: The research concludes that recognizing the legal independence of bodily harm strengthens the protection afforded to injured persons by enabling courts to award compensation that reflects the nature of the injury and its various consequences.